Mellom formidling og fritidsaktivitet. En undersøkelse av vikingtidsformidling ved Borre og Borg - Skudem, Haakon (UiT Norges arktiske universitet, 2019)
This thesis is about the way the viking age is presentet at two norwegian museums dedicated to two specific archaeological sites that is relevant for the period, and their surounding regions. The first museum is Midgard historical centre, later Midgard vikingcentre, connected to the site of Borre, and the region of Vestfold county. The other museum is Lofotr vikingmuseum connected to the site of Borg, and the region of Vestvågøy island. After a carefull analysis of the museums, their purpose, exhibitions and other activities, I have concluded that whilst they do a good job of representing the local context, the same can not be said for the regional.